Single-fed broadband circularly polarized unidirectional antenna using folded plate with parasitic patch for universal UHF RFID readers - Dentri, Sitthichai; Phongcharoenpanich, Chuwong; Kaemarungsi, Kamol (My University, 2016)
This research proposes a simple economical broadband circularly polarized antenna for universal ultra-high frequency (UHF) RF identification (RFID) readers. The antenna utilizes a folded plate, a two-corner truncated parasitic patch, and a ground plane. The folded plate, which is fabricated from one single plate, consists of a two-corner truncated main patch, a wall patch, and a feed line, where the main patch is perpendicular to the wall patch, which is in turn perpendicular to the feed line. The folded plate enables currents to flow with a phase difference. The simulation results achieved an |S11| < −15 dB of 805–966 MHz (18% bandwidth), a 3-dB axial ratio (AR) bandwidth of 834–962 MHz (14% AR bandwidth), and a gain higher than 8.6 dBic. The measured results obtained an |S11| < −15 dB of 806–970 MHz (18%), a 3-dB AR bandwidth of 816–963 MHz (16%), and a gain greater than 7.8 dBic. The proposed antenna is applicable for universal UHF RFID readers as it covers the entire operating UHF RFID frequency range of 840–960 MHz. The parametric study and evolution of the proposed antenna are detailed in this research paper as well. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:575–587, 2016.
Keywords: broadband; circular polarization; UHF RFID